Population genomic analysis uncovers African and European admixture in Drosophila melanogaster populations from the south‐eastern United States and Caribbean Islands. Issue 7 (April 2015) - Kao, Joyce Y.; Zubair, Asif; Salomon, Matthew P.; Nuzhdin, Sergey V.; Campo, Daniel
Abstract: Drosophila melanogaster is postulated to have colonized North America in the past several 100 years in two waves. Flies from Europe colonized the east coast United States while flies from Africa inhabited the Caribbean, which if true, make the south‐east US and Caribbean Islands a secondary contact zone for African and European D. melanogaster . This scenario has been proposed based on phenotypes and limited genetic data. In our study, we have sequenced individual whole genomes of flies from populations in the south‐east US and Caribbean Islands and examined these populations in conjunction with population sequences from the west coast US, Africa, and Europe. We find that west coast US populations are closely related to the European population, likely reflecting a rapid westward expansion upon first settlements into North America. We also find genomic evidence of African and European admixture in south‐east US and Caribbean populations, with a clinal pattern of decreasing proportions of African ancestry with higher latitude. Our genomic analysis of D. melanogaster populations from the south‐east US and Caribbean Islands provides more evidence for the Caribbean Islands as the source of previously reported novel African alleles found in other east coast US populations. We also find the border between the south‐east US and the Caribbean island to be the admixture hot zone where distinctly African‐like Caribbean flies become genomically more similar to European‐like south‐east US flies. Our findings have important implications for previous studies examining the generation of east coast US clines via selection.